STRATEGI PEMBELAJARAN EFEKTIF BIPA UNTUK KELAS PEMULA - Azharin, Barrin (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
BIPA strategies in planning instruction. The 3D animated film strategies and E-book Media plays an important role so that the learning objectives are achieved. Strategies and materials must be composed precisely to achieve effective learning. Pemelajar expected easily understand the material presented by the teacher. elaborasi strategy with election material as well as the preparation of the penyematan elements of the locality so that pemelajar are not too difficult to understand. This is the location of the management strategy and organizing to make it more effective and efficient in putting together learning to suit the purpose.